Immunostimulatory and allergenic properties of emulsified and non-emulsified digestion products of parvalbumin (Scophthalmus maximus) in RBL-2H3 cells and BALB/c mouse models. Issue 12 (13th May 2021) - Luo, Chen; Chen, Guanzhi; Ahmed, Ishfaq; Sun, Lirui; Li, Wenjie; Pavase, Tushar Ramesh; Li, Zhenxing
Abstract : Emulsion with dietary lipids could significantly enhance the allergenicity of PV digestion products. Addition of lipid for processing foods may escalate the potential allergy risk in allergy-prone individuals. Abstract : In the present study, the influence of lipid emulsion on the allergenicity of digestion products of fish parvalbumin (PV) was investigated, which was initially subjected to simulated gastric/intestinal digestion both under emulsified and non-emulsified conditions. The release of β-hexosaminidase (β-hex), histamine (His), tryptase (TPS), interleukin 4 (IL-4), and IL-13 in RBL cells was decreased by 79.32, 26.19, 41.67, 53.95 and 54.40%, respectively, following stimulation with the gastric digestion products of PV. Whereas, lipid emulsified digestion products of PV (e-PV) significantly enhanced the release of active mediators and cytokines. The digestion products of emulsified PV at 180 min resulted in a higher release of β-hex (197.60%), His (12.18%), TPS (38.85%), IL-4 (48.19%) and IL-13 (59.40%), as compared to that of PV. However, no obvious differences in the release of active substances and cytokines were noted between intestinal digestion products of PV and intestinal digestion products of emulsified PV. In the mouse model studies, digested PV products reduced the anaphylactic scores, whereas e-PV manifested a higher level of allergic symptoms. Moreover, mice treated with 50% e-PV had significantly higher levels of specific IgE (32.56%), total IgE (16.67%) and total IgG1 (5.15%) than those treated with 50% PV. Mice treated with 50% e-PV had significantly higher levels of His (8.50%) and TPS (10.07%) compared with mice treated with 50% PV. Lipid emulsions altered the digestibility of PV in gastrointestinal digestion and enhanced the allergenicity of PV digestion products at the cellular levels, subsequently posing a higher risk of allergic reactions in susceptible individuals.